Hemp fiber reinforced one-part alkali-activated composites with expanded perlite: Mechanical properties, microstructure analysis and high-temperature resistance - Kaplan, Gökhan; Turkoglu, Mesut; Tobbala, Dina E.; Bayraktar, Oğuzhan Yavuz; Tayeh, Bassam A. (Elsevier BV, 2023)
The objective of the current research is to find out what impacts hemp fibers (HF) lengths and percentages have on the fresh, physical, mechanical, sorptivity, dry shrinkage, and thermal properties of HF-reinforced alkaliactivated composite (AAC) reinforced with ground blast furnace slag (GBFS). Two groups of AAC mixes with 10 and 20 mm HF lengths were produced. Each group contained different percentages of HF with varying fiber lengths added to mixes at 0.5 %, 1 %, 2 %, and 3.0 % by weight of cement, respectively. Flow diameters were measured to determine the fresh-state properties of the AACs. Water absorption and apparent porosity were determined as physical properties. The unit weights of AAC mixtures are between 1045-1672 kg/m3. Measurements were made on compression and flexural characteristics at 7 and 28 days. The 28-day compressive strengths of AAC mixtures vary between 1.28 and 2.73 MPa, and the bending strengths vary between 0.48 and 1.65 MPa. AAC was also tested for water absorption, drying shrinkage, thermal conductivity, fresh and dry unit weight and porosity. The resistance of high temperatures at 250, 500, and 750 degrees C was determined. There is a significant improvement in compressive and flexural strength and thermal conductivity when HF is added at a 20 mm length. This improvement was confirmed and emphasized through scanning electron microscopy (SEM). According to study results, high-temperature alkali cooking treatments up to 250 degrees C may improve the thermal stability of HF cellulose. The best HF mix, M2-2 %, increased the 28-day compressive strength by 28.8 % and produced the best results at temperatures as high as 750 degrees C. The compressive strength of the mixtures exposed to 750 degrees C was obtained as approximately 2 MPa.